Extensive conservation of alpha and beta chains of the human T-cell antigen receptor recognizing HLA-A2 and influenza A matrix peptide. - Moss, P; Moots, R; Rosenberg, WM; Rowland-Jones, S; Bodmer, H; McMichael, A; Bell, J (1991)
The major histocompatibility complex class I molecule HLA-A2.1 presents the influenza A virus matrix peptide 57-68 to cytotoxic T lymphocytes in all individuals with this common HLA type and is among the most thoroughly studied immune responses in humans. We have studied the T-cell receptor (TCR) heterogeneity of T cells specific for HLA-A2 and influenza A matrix peptide using the polymerase chain reaction. The usage of V alpha and V beta sequences seen on these T cells is remarkably conserved as are certain junctional sequences associated with alpha and beta chains. Furthermore, two unrelated HLA-A2 individuals have a similar pattern of TCR usage, implying that this is a predominant response in HLA-A2 populations. Analysis in one individual showed that the conserved TCR V alpha and V beta genes are minor members of the peripheral blood TCR repertoire. The sequences provide important information on the TCR necessary for the final structural analysis of this ternary complex.